Modeling trade-offs among ecosystem services in agricultural production systems. (October 2015) - Balbi, Stefano; Prado, Agustin del; Gallejones, Patricia; Geevan, Chandanathil Pappachan; Pardo, Guillermo; Pérez-Miñana, Elena; Manrique, Rosa; Hernandez-Santiago, Cuitlahuac; Villa, Ferdinando
Abstract: Although agricultural ecosystems can provide humans with a wide set of benefits agricultural production system management is mainly driven by food production. As a consequence, a need to ensure food security globally has been accompanied by a significant decline in the state of ecosystems. In order to reduce negative trade-offs and identify potential synergies it is necessary to improve our understanding of the relationships between various ecosystem services (ES) as well as the impacts of farm management on ES provision. We present a spatially explicit application that captures and quantifies ES trade-offs in the crop systems of Llanada Alavesa in the Basque Country. Our analysis presents a quantitative assessment of selected ES including crop yield, water supply and quality, climate regulation and air quality. The study is conducted using semantic meta-modeling, a technique that enables flexible integration of models to overcome the service-by-service modeling approach applied traditionally in ES assessment. Highlights: The intensification and extensification of agriculture threatens ecosystems globally. An ecosystem-based approach to food provision is shown for a specific Basque case. Three ES are integrated with crop production into a modular agri-modeling framework. Improving air and water quality by reducing manure usage implies major yield losses. Avoiding tillage increases carbon sequestration with marginal impacts on yields.